2002
DOI: 10.1021/ic020178h
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Gold(I) Thiobarbiturate Chemistry:  Combining Aurophilicity and Hydrogen Bonding to Make Polymers, Sheets, and Networks

Abstract: The cooperative forces of aurophilic and hydrogen bonding have been used in the self-assembly of phosphine or diphosphine complexes of gold(I) with the thiolate ligands derived from 2-thiobarbituric acid, SC(4)H(4)N(2)O(2), by single or double deprotonation. The reaction of the corresponding gold(I) trifluoroacetate complex with SC(4)H(4)N(2)O(2) gave the complexes [Au(SC(4)H(3)N(2)O(2))(PPh(3))], 1, [(AuSC(4)H(3)N(2)O(2))(2)(micro-LL)], with LL = Ph(2)PCH(2)PPh(2), 2a, Ph(2)P(CH(2))(3)PPh(2), 2b, or Ph(2)PCH=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(58 citation statements)
references
References 58 publications
3
54
1
Order By: Relevance
“…Regarding the latter, it has been concluded that the layers consist of hexagonally arranged gold and sulfur atoms with arrays of the peptide ligands bulging perpendicularly to the plane [29]. In other works on Au-thiolates such as Au-thiomalate or Au-phenylthiolate, zigzag shaped chains of the polymers with and alternating arrangement of ligand molecules have been proposed [13,32,33]. Luminescent gold(I) acetylides with the same shape have been reported [34].…”
Section: ) This Is In Correspondence With the Characteristic Emissmentioning
confidence: 96%
“…Regarding the latter, it has been concluded that the layers consist of hexagonally arranged gold and sulfur atoms with arrays of the peptide ligands bulging perpendicularly to the plane [29]. In other works on Au-thiolates such as Au-thiomalate or Au-phenylthiolate, zigzag shaped chains of the polymers with and alternating arrangement of ligand molecules have been proposed [13,32,33]. Luminescent gold(I) acetylides with the same shape have been reported [34].…”
Section: ) This Is In Correspondence With the Characteristic Emissmentioning
confidence: 96%
“…The intramolecular AuÀAu distance is 3.336(1) , which is essentially identical to the distance be- The structural and functional similarities of aurophilic and hydrogen bonding have been emphasized in recent studies. [28] In particular, a striking structural similarity between isocyanide complexes MeA C H T U N G T R E N N U N G (CH 2 ) nÀ1 NCAuCl and primary…”
Section: A C H T U N G T R E N N U N G {C 5 H 4 a C H T U N G T R E Nmentioning
confidence: 99%
“…[30][31][32][33][34][35][36] In addition to coordinative bonding, a multitude of interactions have been used in the synthesis of periodic networks including covalent bonding, [37] hydrogen bonding, [38][39][40] p-p interactions, [41][42][43] ionic interactions, [44,45] lipophilic interactions, [46,47] metalmetal interactions, [48][49][50] and halogen bonding. [51,52] However, the deliberate use of cation-p interactions to control the assembly of extended networks has received little attention.…”
Section: A C H T U N G T R E N N U N G Lua C H T U N G T R E N N U N mentioning
confidence: 99%